-1=b/5+2-2

Simple and best practice solution for -1=b/5+2-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=b/5+2-2 equation:



-1=b/5+2-2
We move all terms to the left:
-1-(b/5+2-2)=0
We add all the numbers together, and all the variables
-(+b/5)-1=0
We get rid of parentheses
-b/5-1=0
We multiply all the terms by the denominator
-b-1*5=0
We add all the numbers together, and all the variables
-1b-5=0
We move all terms containing b to the left, all other terms to the right
-b=5
b=5/-1
b=-5

You can always share this solution

See similar equations:

| 6+21/a=13 | | y-2y+4=8 | | 27/y+3=6 | | 4/3x-1/2=2(1/6x-4) | | 4+30/a=9 | | n+33-15+20=21 | | 4x+28=8x-4= | | 2(3x-4)=4(1/8x-8) | | 7-u/9=2 | | -3.5+p/7=-52 | | 7+x/9=10 | | 60/c-3=3 | | 60=30+2x | | 4/a+3=5 | | 8-b/9=3 | | 2m+6(m-3)=-14 | | 8-z/9=2 | | 12-(x)(7)=23 | | 64/c+1=9 | | 1748+600p=1808 | | (3x+25)°2x°=56 | | 11.5-3y=4 | | 4+u/5=12 | | 10k-9=100 | | 10+5/b=15 | | 8+32/a=16 | | 4x-5+2(x-3)=x+7 | | 2x-4(x-3)=-9+3x+11 | | 8=-4x-16 | | 18(n-3)=82 | | x2+20=12x | | 72/a-4=5 |

Equations solver categories